ANALYSIS OF THE RELEVANCE OF SPIRITUALITY AMONG PSYCHOLOGY STUDENTS AT UNIEVANGÉLICA AS A FACTOR FOR PRESERVING MENTAL HEALTH THROUGHOUT UNDERGRADUATE COURSE (CIPEEX, 2026)
Introduction: Psychology students experience a highly emotionally demanding environment during their undergraduate studies, making them vulnerable to stress and other common mental disorders. In this sense, spirituality and religiosity are potential protective factors for mental health. Objective: To analyze the academic reality of UniEVANGÉLICA Psychology students in relation to mental health, identifying the influence of spirituality. Method: This is a descriptive, cross-sectional, qualitative study conducted with 35 students from the 1st, 4th, and 8th semesters. A socioeconomic questionnaire and the DASS-21, SSRS, FACIT-SP, and WHOQOL-SRPB scales were administered. Results: Most students presented high levels of spirituality and spiritual perception, which was associated with lower rates of depression, anxiety, and stress. A negative correlation was observed between spirituality and psychological distress (r ranging from -0.26 to -0.39), suggesting that the greater the spirituality, the lower the negative symptoms of depression, anxiety, and stress. Conclusion: Spirituality proved to be a relevant protective factor for the mental health of Psychology students.
Keywords: Espiritualidade; Estudantes Universitários; Saúde Mental